The Relationship Between Family Social Capital and Students’ Tolerance in the Context of Social Diversity: A Quantitative Study in Pontianak - M Zainul Hafizi; Aminuyati; Sahidi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
The high level of social diversity in Pontianak City demands the strengthening of tolerance character among the younger generation, while the family is believed to serve as the primary foundation for shaping children’s social attitudes. This study aims to analyze the relationship between family social capital and the tolerance character of high school students in Pontianak City. A quantitative approach was employed using a survey design. The study involved 405 high school students selected through random sampling. Data were collected via a closed-ended questionnaire based on a five-point Likert scale, covering constructs of family social capital and students’ tolerance character, and were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The findings revealed a very strong and significant relationship between family social capital and students’ tolerance character, with family social capital contributing 59.7% to the variance in students’ tolerance character. However, the average level of students’ tolerance character remains moderate, indicating the need for broader interventions. These results emphasize the crucial role of the family in cultivating tolerance values but also highlight the necessity for collaborative efforts among families, schools, and communities. This study contributes to the understanding of character education development based on family social capital within multicultural contexts and offers insights for more comprehensive educational policy formulation